MANAJEMEN PEMBELAJARAN AGAMA DAN KEAGAMAAN DI ERA INDUSTRI 4.0 - Saefudin Zuhri (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
Industrial era 4.0 became a big chalangge for educators especially for religious and religious subjects or Islamic Educators. Because in addition to teaching religious content that is mandatory for Muslim believers, Islamic Religious Education must also teach that instruct muslim to be creative and innovative, along with teaching about inclusiveism in order to collaborate across ethnic, cultural and religious group in facing the area of disruptive innovation. Which is an opportunity for anyone to pay attention to linearity. Industry 4.0 as the CPS, IoT, and IoS era, has been very systemic, and every industry does not need many people, except computer operators, production network supervisors and all related to computer work control. Therefore, they must be creative people to develop entrepreneurship, or services that are needed by society. Opportunity to be able to do entrepreneurial works is huge, because the world now ignores linierity, instead appreciates more creativity and networking capabilities. Therefore, educators must educate their students, and lecturers also direct their students to be realistic and become creative people. Creative and innovative education has no subjects. Therefore, fostering and enhancing their creativity is done through pendagogy for all subjects, especially subjects such as Islamic Education in schools or universities, so that they can get used to being creative and innovative people. As well as, inclusivism must be forestered and forested through a learning process that touches on aspect of attitude or affective trough discussion and or other techniques that enchance the competencies or learners in collaborating across ethnic, cultural and religious backgrounds.